Carbonate biomineralization differentially induced by two psychrophilic Pseudomonas psychrophila strains isolated from an alpine travertine landform. Issue 21 (6th April 2021) - Song, Na; Li, Qiongfang; Zhou, Yi; Sun, Geng; Pan, Ling; Zhao, Xiaoxia; Dong, Pengju; Zhao, Yulian; Yang, Lijun; Huang, Yunbi
Abstract : Calcium carbonate crystals induced by two Pseudomonas psychrophila strains and their organic compounds were studied. Abstract : Besides geography and climate, biological factors play an important role in shaping travertine landforms, but the biochemical mechanisms of microbial processes in travertine formation have been rarely studied. Two psychrophilic bacterial strains, A20-18 and B21-3 of Pseudomonas psychrophila, isolated from travertine pools of Huanglong, a typical alpine travertine landform, were investigated for their roles in calcium carbonate mineralization, including the deposition process and products. X-ray diffraction, Fourier-transform infrared spectroscopy, and scanning electron microscopy were used to characterize the crystal phase and morphology of CaCO3 precipitation. The results showed that there were no significant differences between the two strains in CaCO3 deposition rate. Extracellular polymeric substances (EPS)-free cells significantly inhibited calcification, compared with a control. Irregular crystals and polyhedral structures are common to all treatments using the two strains. These complex polycrystals were the result of the synergistic effect of homogeneous nucleation and heterogeneous nucleation. EPS and cells of strain B21-3 formed ring-like structures of calcium carbonate, which was possibly from the amphiphilic polymer forming a circular arrangement in water. These results are significant for understanding the microbial factor in Huanglong travertine deposition and providing new insights into the morphological control of the biomineralization mechanism at low temperatures.